Protein interactions at the higher plant nuclear envelope: evidence for a linker of nucleoskeleton and cytoskeleton complex - Evans, David E.; Pawar, Vidya; Smith, Sarah J.; Graumann, Katja (Frontiers in Plant Science, 2014)
Following the description of SAD1/UNC84 (SUN) domain proteins in higher plants, evidence has rapidly increased that plants contain a functional Linker of Nucleoskeleton and Cytoskeleton (LINC) complex bridging the nuclear envelope (NE). While the SUN domain proteins appear to be highly conserved across kingdoms, other elements of the complex are not and some key components and interactions remain to be identified. This mini review examines components of the LINC complex, including proteins of the SUN domain family and recently identified plant KASH domain proteins. First of these to be described were WIPs (WPP domain Interacting Proteins), which act as protein anchors in the outer NE. The plant KASH homologs are C-terminally anchored membrane proteins with the extreme C-terminus located in the nuclear periplasm; AtWIPs contain a highly conserved X-VPT motif at the C-terminus in contrast to PPPX in opisthokonts. The role of the LINC complex in organisms with a cell wall, and description of further LINC complex components will be considered, together with other potential plant-specific functions.